A longitudinal examination of elite athlete well-being - Clancy, R.; Herring, M. P.; Campbell, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Elite athletes operate in demanding environments that consistently stretch their physical, psychological and emotional limits, and increase susceptibility to maladaptive behaviours/outcomes (e.g., disordered eating, burnout), reinforcing the need for ongoing psychological monitoring. Subjective measures of mood and mental health can be particularly useful tools, which may be indicative of future performance and provide guidance for titrating training load. Thus, this study characterised the mood and mental health profile of elite athletes, longitudinally examined these outcomes and their interrelations, and explored potential moderators (e.g., type of sport, gender, and age). Methods: Elite team sport athletes (N=136) aged 18-37 years (23.21±4.56) with an average of 12.77±5.13 years sport experience were assessed using psychometric inventories over a 13-week period (compliance = ~94%). The sports represented were basketball, Gaelic football, field hockey, hurling, rowing, rugby, and soccer. Outcomes included the Profile of Mood States-Brief and Quick Inventory of Depressive Symptomatology (QIDS), administered weekly, and the Pittsburgh Sleep Quality Index (PSQI) and the trait subscale of the State-Trait Anxiety Inventory (STAI-Y2), administered every four weeks. Missing data was accounted for using Last Value Carried Forward imputation. Results: The average Total Mood Disturbance (TMD) was 4.3 (SD=8.7), which is lower than that of similarly-aged Americans (26.1±15.9, Yeun & Shin Park, 2006). 18.4% of athletes were classed as having mild depression across the 13 weeks (QIDS=6.3). 39.7% and 7.4% of athletes were categorised as poor quality sleepers (PSQI>5) and highly trait anxious (STAI-Y2>50), respectively. Nine of the ten athletes who were highly trait anxious and 19/25 athletes with mild depression were also poor sleepers. There was a significant difference in TMD for Gaelic (1.4±7.6) and non-Gaelic (5.6± 8.7) sports (t134=2.62, p 0.01). There were no significant differences by gender or five-year age group for any outcome. Discussion: Measures of mood and mental health change and influence each other among elite athletes over a 13-week period. Monitoring such outcomes appears to be informative, as those with maladaptive behaviours (e.g., poor sleep quality) can be identified for intervention. Subjective measures of mood and mental health outcomes are easy to administer and may prove useful to guide training load adjustments and indicate future performance among team sport athletes.